Association of the lncRNA HOTAIR Gene rs4759314 with Susceptibility to Recurrent Spontaneous Abortion in a Chinese Han Population - Luo, Binglai; Liu, Xiaoli; Huang, Jiangang; Wang, Jinyong (The Tohoku Journal of Experimental Medicine, 2025)
This study was to examine the association between the long noncoding RNA (lncRNA) HOTAIR polymorphism (rs4759314, rs4759314) and the risk of recurrent spontaneous abortion (RSA) in Chinese Han women. 378 women with RSA and 361 pregnant women with normal pregnancies were selected as study subjects. The expression level of lncRNA HOTAIR was detected by fluorescence quantitative PCR. PCR restriction fragment length polymorphism (PCR-RFLP) method was used to detect genotyping. Logistic regression analysis was used to assess the independent factors of HOTAIR rs4759314 affecting recurrent miscarriage. The lncRNA HOTAIR gene expression level was significantly reduced in RSA patients. Rs1899663 polymorphism and rs4759314 GG genotype do not significantly increase the risk of developing RSA (P > 0.050). Rs4759314 AG genotype and rs4759314G allele significantly increased the risk of developing RSA (P < 0.050). Logistic analysis showed a significant correlation between rs4759314 and the occurrence of RSA (OR = 0.367, 95% CI = 0.232-0.580, P < 0.050). The lncRNA HOTAIR rs4759314 locus may serve as a biomarker for RSA susceptibility in the Chinese Han population.